Development of the immunoenzyme test system for detection of antibodies against avian leukosis virus - S. P. Lazareva; M. A. Volkova; N. S. Mudrak; I. A. Chvala; T. V. Zhbanova (Ветеринария сегодня)
Test system based on the immunoenzyme method was developed for detection of antibodies to the avian leukosis virus (ALV) when testing sera in a single dilution. The antibody titer was determined basing on S/P ratio calculated for one working serum dilution (1:400). The developed test system demonstrated high specificity and sensitivity in comparison with the foreign commercial kit.